Woven with Water - Chidyaonga, Nicola (Faculty of Engineering and the Built Environment, 2023)
The Elephant Marsh is a seasonal wetland that lies on the floodplain of the Lower Shire River in Malawi. This is one of the most productive ecosystems in Malawi that plays an important role in supporting the livelihoods of the local community (Kosamu, 2012) through fisheries, livestock grazing, and agriculture. The Elephant Marsh also plays a significant role in flood storage, attenuation, and purifying sediment-rich water. Furthermore, it is a habitat for over 110 water bird species (Bayliss, 2019). Unfortunately, upstream development, commercial sugarcane farming, human encroachment, and severe land degradation such as soil erosion, sedimentation, and deforestation within the Shire River Basin have resulted in a decline in remaining natural areas which have led to a decrease in infiltration and water holding capacity in the basin. This project aims to create a resilient system using fingerponds and rainwater harvesting practices that embrace the process of flooding and precipitation during the wet season by holding water and allowing it to infiltrate into the landscape. Furthermore, the project aims to reconnect the riparian community to a century-old traditional practice of harvesting and weaving reeds and palm leaves into mats and baskets to allow for a deeper relationship to form between the people and place while also creating more opportunities for the community. The term landscape resilience in this project is an aspect of wet theory, which is a way of accommodating flow and other boundary-blurring phenomena of motion, disturbance, and change through fluid occupancies of land and infiltration (Mathur & Da Cunha, 2009). Furthermore, the resilient landscape in this project is also linked to the preservation of traditional knowledge systems that are connected to the landscape to ensure the long-term success of the proposed sustainable practices. Through research, a site visit, and interviews, the study first uncovers the sense of place and identity of the landscape. Elements of the site are then synthesized through map analysis and visual narratives to understand the different relationships between the social and ecological aspects of the site. Finally, these relationships are then tested in a design intervention that aims to accommodate for uncertainty and forms a more integrated agriculture, aquaculture, and traditional system that retains the functioning of the wetland improves the wetland edge and empowers the community.